ANALISIS BEBAN TEKUK KRITIS STRUKTUR SANDWICH BAHAN KOMPOSIT PADA SIRIP ROKET RX LAPAN - Putra, Ronald Gunawan (BRIN Publishing, 2005)
The using of sandwich structure on the tail of RX LAPAN Rocket offers several advantages compared to conventional structure, such as lightweight, higt stiffiness and good fatigue property. But, one of the problems is its weakness under compressive loads, especially when there is a delaminated area. Buckling modes that often occur in sandwich structure due to compressive loads is overall buckling. This paper will analyze the influence of delamination over critical buckling load with finite element method using 2-D modeling.